زراعة الجينات وتوجيه صفات الأجنة الدوافع والحكم الشرعي - صالح رشاد زيد الكيلاني, رشاد (University of Eloued جامعة الوادي, 2014)
يعالج هذا البحث مسألة طبية معاصرة تعنى بتوجيه الصفات الوراثية من خلال زراعة الجينات؛ وتنطلق الدراسة من عرض السياق التاريخي وتقديم نبذة عن فكرة توجيه صفات الأجنة؛ ثم تتطرق للسياق العلمي لفكرة توجيه صفات الأجنة؛ وتخلص بعد التوصيف إلى السياق الشرعي لفكرة توجيه صفات الأجنة وبيان الحكم الشرعي مؤيدا بأدلته ومبرراته الموضوعية. This research deals with a contemporary medical issue relating to genetic traits through the transplanted genes. This research deals with the historical context of this issue and give an overview of the idea of directing qualities embryos. It also addresses the scientific context to the idea of directing qualities embryos. Finally, the research deals with the legitimate context of the idea of directing qualities embryos and it indicates the Islamic ruling.
مقال بمجلة البحوث والدراسات
Keywords: الجينات – الهندسة الوراثية – زراعة الجينات- التحكم في الجينات – الحكم الشرعي; genes - genetic engineering - transplanted genes - genes control –Legal (shar'i) ruling.